2020
DOI: 10.1080/07391102.2020.1757510
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-like and small-molecule inhibitors against Covid-19

Abstract: Coronavirus disease strain (SARS-CoV-2) was discovered in 2019, and it is spreading very fast around the world causing the disease Covid-19. Currently, more than 1.6 million individuals are infected, and several thousand are dead across the globe because of Covid-19. Here, we utilized the in-silico approaches to identify possible protease inhibitors against SARS-CoV-2. Potential compounds were screened from the CHEMBL database, ZINC database, FDA approved drugs and molecules under clinical trials. Our study is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
225
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(238 citation statements)
references
References 30 publications
4
225
0
1
Order By: Relevance
“…Finally, MD simulation was performed for 100 ns long and snapshots were saved at every 100 ps into MD trajectory for further analysis. Root-mean-square deviation (RMSD), rootmean-square fluctuation (RMSF), radius of gyration (Rg), solvent accessible surface area (SASA), and total number of Hbond count were calculated from the MD simulations similar to other studies (Elfiky & Azzam, 2020;Enayatkhani et al, 2020;Muralidharan et al, 2020;Pant et al, 2020).…”
Section: Molecular Dynamicsmentioning
confidence: 99%
“…Finally, MD simulation was performed for 100 ns long and snapshots were saved at every 100 ps into MD trajectory for further analysis. Root-mean-square deviation (RMSD), rootmean-square fluctuation (RMSF), radius of gyration (Rg), solvent accessible surface area (SASA), and total number of Hbond count were calculated from the MD simulations similar to other studies (Elfiky & Azzam, 2020;Enayatkhani et al, 2020;Muralidharan et al, 2020;Pant et al, 2020).…”
Section: Molecular Dynamicsmentioning
confidence: 99%
“…(Doublie & Ellenberger, 1998;Elfiky, 2020a;Elfiky & Ismail, 2018). Several studies are suggesting the effectiveness of different anti-viral drugs and compounds against the coronavirus proteins (Aanouz et al, 2020;Boopathi et al, 2020;Elfiky & Azzam, 2020;Elmezayen et al, 2020;Enayatkhani et al, 2020;Gupta et al, 2020;Khan et al, 2020aKhan et al, , 2020bMuralidharan et al, 2020;Pant et al, 2020;Sarma et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Among all the treatment strategies, the uses of already known viral medications have great advantages as the pharmacokinetics, pharmacodynamics, and safety profiles of these drugs have already been established. This drug repurposing strategy has gained significance as they are expected to be faster with less investment (Fitchett et al, 2014;Law et al, 2013;Pant et al, 2020;Park, 2019). Preliminary studies revealed Lopinavir/ritonavir combined therapy as a potential inhibitor of the virus.…”
Section: Introductionmentioning
confidence: 99%